2018
DOI: 10.1007/s00296-018-4221-z
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical and ultrastructural analysis of sporadic inclusion body myositis: a case series

Abstract: Sporadic inclusion body myositis (s-IBM) is a progressive, skeletal muscle disease with poor prognosis. However, establishing the final diagnosis is difficult because of the lack of clear biomarkers in the blood serum and very slow development of clinical symptoms. Moreover, most other organs function normally without any disturbance. Here, in patients with this untreatable disease, we have underlined the importance of immunohistochemical and ultrastructural assessment of skeletal muscle in patients diagnosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
(103 reference statements)
0
5
0
Order By: Relevance
“…In IBM, amyloid-beta shows a tendency to accumulate in distal muscles in the present study. In support of this finding, Haczkiewicz et al reported that abnormal pathological findings compatible with s-IBM were detected even in the gastrocnemius muscle of their s-IBM patient, although the presence of amyloid deposition was unclear in the muscle (9).…”
Section: Discussionmentioning
confidence: 70%
“…In IBM, amyloid-beta shows a tendency to accumulate in distal muscles in the present study. In support of this finding, Haczkiewicz et al reported that abnormal pathological findings compatible with s-IBM were detected even in the gastrocnemius muscle of their s-IBM patient, although the presence of amyloid deposition was unclear in the muscle (9).…”
Section: Discussionmentioning
confidence: 70%
“…A competing hypothesis is that IBM is primarily a degenerative disease, analogous to neurodegenerative diseases. This view is supported by ultrastructural characterization of the inclusions in IBM which form amyloid-like fibrils and tubulofilaments analogous to those observed in the brain in Alzheimer's disease (AD) (16). Indeed, intracellular -amyloid accumulation is observed in IBM muscle, and overexpression of amyloid  precursor protein (APP) in human myoblasts or mouse muscle causes toxicity (17,18).…”
Section: Introductionmentioning
confidence: 87%
“…Muscle biopsy and staining show variation in the fiber size, type II fiber atrophy, endomysial infiltrates, and infiltration of inflammatory infiltrate into non‐necrotic muscle fibers. Immunohistochemistry and Engel's trichrome stain show increased expression of major histocompatibility complex 1 and cytoplasmic red‐rimmed vacuoles, respectively 51 . Electron microscopic studies suggest tubulo‐filamentous inclusions in the cytoplasm, 52 with identification of the contents, location and function using special stains such as TDP43, LC3 and p62 53 .…”
Section: Investigationsmentioning
confidence: 99%
“…Immunohistochemistry and Engel's trichrome stain show increased expression of major histocompatibility complex 1 and cytoplasmic red-rimmed vacuoles, respectively. 51 Electron microscopic studies suggest tubulo-filamentous inclusions in the cytoplasm, 52 with identification of the contents, location and function using special stains such as TDP43, LC3 and p62. 53 Since rimmed vacuoles may not always be present on a muscle biopsy, the higher presence of cyctochrome C oxidase -succinate dehydrogenase + fibers in IBM as compared with polymyositis (PM) or dermatomyositis (DM) may be discriminative, with an area under the curve of 0.93 for diagnosis.…”
Section: Inve S Tig Ationsmentioning
confidence: 99%